Meta‐analysis of subjective complaints of vertigo and vestibular tests after cochlear implantation. (4th January 2018) - Hänsel, Toni; Gauger, Ulrich; Bernhard, Nikolai; Behzadi, Nina; Romo Ventura, Maria Eugenia; Hofmann, Veit; Olze, Heidi; Knopke, Steffen; Todt, Ingo; Coordes, Annekatrin
Abstract : Objective: Postoperative vertigo is a common complaint after cochlear implantation, but published incidence rates differ vastly. The aim of the present study was to investigate both subjective complaints of vertigo before and after cochlear implantation and related vestibular diagnostic tests on cochlear implant candidates. Data Sources: We performed a systematic literature search according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement in PubMed, Cochrane Register, and EMBASE. Review Methods: We presented 116 eligible studies investigating subjective complaints of vertigo after cochlear implantation and/or related vestibular diagnostic tests. We conducted three meta‐analyses of 46 eligible studies with matched pre‐ and postoperative data to calculate the odds ratio of new vertigo onset, as well as the impairment of vestibular receptors measured by nystagmography and cervical vestibular evoked myogenic potentials (cVEMP). Postoperative vertigo was calculated from 95 studies and further subdivided by mean age with pooled data. Results: We observed a significant increase in postoperative vertigo and significant impairment of nystagmography and cVEMP detection. Vertigo after cochlear implantation was reported in 9.3% of the patients with a continuous increase in patient age at surgery. In a subgroup of studies, new onset of vertigo was found in 17.4% of the patients. In addition, 7.2% of the patients had persisting vertigo complaints, whereas 11.6% described an altered vertigo quality and 7.7% had their preoperative complaints resolved. A comparison of round window approach and cochleostomy revealed significantly increased vertigo after cochleostomy. Both insertion methods showed similar effects in nystagmography and cVEMP testing. Conclusion: Cochlear implantation has a significant impact on subjective vertigo and vestibular receptor function. This is affected by the patient's age at the time of surgery. The surgical technique (round window or cochleostomy) may influence the outcome, but this requires further investigation. Younger patients may compensate better following vestibular dysfunction. Perioperative testing is required to correlate vestibular impairment and subjective complaints. Laryngoscope, 2018 Laryngoscope, 128:2110–2123, 2018